Chapter Il turista, il Baedeker e il viaggiatore. Il viaggio e i viaggiatori secondo Abel Salazar - Da Silva Valente, Carla Marisa (Studi e saggi, 2021)
Abel Salazar presents the considerations of a traveler-storyteller about some Italian cities in his book of travel narratives, Uma Primavera em Itália (2003), the central corpus of our research. Starting from an introduction about the author, the text, the perspectives of travel literature in the first half of the twentieth century, its categorization and reflecting on the tourist and traveler profile, we intend, with this research, to present a critical analysis of the interpretation of the figure of the traveler and its facets by the eclectic Portuguese author Abel Salazar, praised and criticized in his travel narratives.